2012
DOI: 10.1111/j.1399-0004.2012.01951.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the utility of whole‐exome sequencing as a diagnostic tool in a child with atypical episodic muscle weakness

Abstract: The advent of whole-exome next-generation sequencing (WES) has been pivotal for the molecular characterization of Mendelian disease; however, the clinical application of WES has remained relatively unexplored. We describe our experience with WES as a diagnostic tool in a three-year old female patient with a two-year history of episodic muscle weakness and paroxysmal dystonia who presented following a previous extensive but unrevealing diagnostic work-up. WES was performed on the proband and her two parents. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…31,[33][34][35] In our study, we showed that the coverage of a predefined list of genes associated with dHMN and overlapping disorders was sufficiently high to use exome sequencing as an initial diagnostic approach. In addition, the combined use of Sequenom MassARRAY to validate the genetic variants identified appeared to be a fast and powerful strategy.…”
Section: Discussionmentioning
confidence: 84%
“…31,[33][34][35] In our study, we showed that the coverage of a predefined list of genes associated with dHMN and overlapping disorders was sufficiently high to use exome sequencing as an initial diagnostic approach. In addition, the combined use of Sequenom MassARRAY to validate the genetic variants identified appeared to be a fast and powerful strategy.…”
Section: Discussionmentioning
confidence: 84%
“…CACNA1S pathogenic variants have been identified as the cause of hypokalemic periodic paralysis type 1 (HOKPP1) (Burge and Hanna 2012; Hanchard et al. 2013), but persistent weakness of the child is somewhat inconsistent with HOKPP1. While it has been suspected that CACNAS1 variants could cause myopathies due to the physical and mechanical coupling between its gene product, the voltage-dependent L-type calcium channel subunit alpha-1S (Cav1.1), and the Ryanodine receptor Ca 2+ release channel 1 (RYR-1)(Wu et al.…”
Section: Resultsmentioning
confidence: 92%
“…Pathogenic variants in CACNA1S have been identified as a cause of HOKPP1, but RYR1 have not (Burge and Hanna 2012; Hanchard et al. 2013). Pathogenic variants in RYR1 are the most common causes of CCD, while CACNA1S have not been identified as a cause of CCD (Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Mutations in the mitochondrial alanyltRNA synthetase 2 gene (AARS2; OMIM *612035) have been found in severe infantile cardiomyopathy in 2 families. 9 In the present study, we describe a very different clinical picture determined by AARS2 genetic defects in 6 patients affected by a progressive leukoencephalopathy and, in females, ovarian failure, a clinical presentation previously described as "ovarioleukodystrophy."…”
mentioning
confidence: 99%